1997
DOI: 10.1016/s1074-7613(00)80387-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of EBV Immortalization Precedes Apoptosis in IL-6–Induced Human B Cell Terminal Differentiation

Abstract: Cell death in B cell terminal differentiation rapidly follows cell cycle arrest in IL-6 differentiation of EBV-immortalized, IgG-bearing human lymphoblastoid cells in vitro. G1 arrest is now found to coincide with repression of EBNA2 and LMP1, two EBV genes essential for B cell transformation, without activation of the viral lytic cycle. IL-6-differentiated B cells die by apoptosis, as evidenced by increases in Annexin V binding activity, PARP cleavage, and chromatin disorganization. Expression of Mcl-1, a Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 70 publications
6
47
0
Order By: Relevance
“…We found that overexpression of Mcl-1 protected CE81T/VGH cells from staurosporine-induced apoptosis and transfection of a Mcl-1 antisense plasmid substantially increased the percentage of apoptotic cells (Figure 7). Our data support the fact that Mcl-1 is an inducible, antiapoptotic protein, as previously described in myeloid cells induced by TPA and GM-CSF (Kozopas et al, 1993;Chao et al, 1998), and in EBV immortalized B cells induced by IL-6 (Altmeyer et al, 1997). While the induction of Mcl-1 by TPA was mediated through the MAP kinase pathway in myeloblastic leukemia cells (Townsend et al, 1998), the IL-3 activation of mcl-1 gene expression was mediated via PI3-K-Akt-dependent andindependent pathways in murine pro-B Ba/F3 cells (Wang et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…We found that overexpression of Mcl-1 protected CE81T/VGH cells from staurosporine-induced apoptosis and transfection of a Mcl-1 antisense plasmid substantially increased the percentage of apoptotic cells (Figure 7). Our data support the fact that Mcl-1 is an inducible, antiapoptotic protein, as previously described in myeloid cells induced by TPA and GM-CSF (Kozopas et al, 1993;Chao et al, 1998), and in EBV immortalized B cells induced by IL-6 (Altmeyer et al, 1997). While the induction of Mcl-1 by TPA was mediated through the MAP kinase pathway in myeloblastic leukemia cells (Townsend et al, 1998), the IL-3 activation of mcl-1 gene expression was mediated via PI3-K-Akt-dependent andindependent pathways in murine pro-B Ba/F3 cells (Wang et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…These cells concomitantly downregulate EBNA-1, EBNA-2 and LMP-1. 39 Furthermore, normally a small fraction of cells in LCLs express cytoplasmic Ig, lack EBNA-2 and cease to proliferate. 40 While the EBV expression type of the KMH2 EBV subline did not correspond to that of in vivo H/RS cells, LMP-1 expression was induced by exposure to IL-4 and CD40 ligand both in the EBV-positive established line and in freshly infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Repression or absence of several of the genes listed in Table 2 has been reported to promote apoptosis, e.g. for Survival of Motor Neurons (SMN; Schrank et al, 1997), myeloid cell di erentiation protein (Mcl-1; Altmeyer et al, 1997;Moulding et al, 1998) or receptorassociating protein of 46 kDa (RAP46; Kullmann et al, 1998).…”
Section: Discussionmentioning
confidence: 99%